Perencanaan Strategi Sekolah Internasional dalam Meningkatkan Mutu Pendidikan - Nurmadiah, Nurmadiah (UMSU, 2024)
This study aims to determine and analyze the strategic planning, strategy implementation, and strategy evaluation of school principals in improving the quality of education. This type of research is qualitative, uses a descriptive approach and is based on a case study. Data collection and using interview, observation and documentation techniques. The results of the study are linking the approach to: a) formulating the vision and mission, b) identifying goals that guide to the mission, c) determining goals in helping to achieve goals, and d) making work plans (Renstra) that encourage the achievement of goals. In addition, strategic planning can be done by using SWOT analysis in measuring or evaluating activities in organizational/school units by evaluating Strengths, Weaknesses, Opportunities and Threats. Planning begins with the principal's commitment to improving the quality of education, followed by revamping the organizational structure of the school and committee, improving the competence of educators and education personnel, fulfilling facilities and infrastructure, building networks and creating excellent service programs.